Hate Speech On Social Media: An Integrated Analysis Of Forensic Linguistics and Indonesian Criminal Law - Anita Puspawati (Jurnal Ilmu Sosial dan Humaniora, 2026)
Social media has become a basic need for social interaction, yet users often fail to realize that what they write can constitute hate speech, making it important to understand the intent behind an utterance. This is a normative legal study using a statute and conceptual approach combined with a forensic linguistic approach, drawing on primary legal materials including the Criminal Code, the Law on Electronic Information and Transactions, Law Number 40 of 2008 on the Elimination of Racial and Ethnic Discrimination, and Police Chief Circular Letter Number SE/6/X/2015. Hate speech is a multidisciplinary issue spanning legal, linguistic, and communicative aspects. Legally, it can be criminally punished if it fulfills the elements set out in statutory regulations; linguistically, analysis focuses on meaning, context, and purpose using Grice’s Cooperative Principle and Leech’s Politeness Principle as the pragmatic framework. Analysis of two court decisions shows that classifying an utterance as hate speech cannot rely on lexical meaning alone but must account for context, implicature, and speaker intent, so that integrating pragmatic and legal analysis produces a more objective, proportional basis for law enforcement.